Immunohistochemical detection of African swine fever and classical swine fever virus antigen from formalin-fixed paraffin-embedded swine tissues - Uda Zahli, Nurul Izzati; Che' Amat, Azlan; Fong, Michelle Wai Cheng; Ooi, Peck Toung; Phan, Y.W. (Malaysian Veterinary Medical Association, 2024)
African swine fever was first reported in February 2021 and shares similar pathological signs with classical swine fever, which is endemic in Malaysia. This study aimed to detect the viral antigen in formalin-fixed paraffin-embedded (FFPE) tissue samples using immunohistochemistry and to characterise the histopathological lesions. The FFPE tissues of spleen, tonsil and lymph nodes of 17 domestic pigs and three wild boars were collected from 2020 to 2022 from the histopathology laboratory archive. Immunohistochemistry revealed ASFV antigen-positive cells in 1/20 (5%) samples and CSFV antigen-positive cells in 4/20 (20%) samples. All CSF-positive samples show lymphoid depletion in the tonsil, lymph node and spleen tissues and 3/4 (75%) show haemorrhages in lymph node and spleen tissues. This study illustrates the need to strengthen biosecurity to prevent transmission of ASF and CSF into the farm.